BEBAN KERJA, KETIDAKAMANAN KERJA, KESEJAHTERAAN PSIKOLOGIS DAN STRES KERJA - Roni Wahyu,; Hardani Widhiastuti ,; Mulya Virgonita Iswindari Winta , (Journal of Innovation Research and Knowledge, 2025)
Job stress is adaptive response influenced by personal characteristics and psychological processes result of external actions, situations or events impose physical and psychological demands on employees. For this reason, organizations must pay attention to fostering good relations with employees because no matter how good strategy made organization will not be implemented properly if its not accompanied a positive attitude from employees. This study aims to determine effect workload and job insecurity on work stress with psychological well-being as an intervening variable, number subjects is 85 technician employees PT Telkom Access Semarang who are determined using random sampling. Variables this study are workload, job insecurity, psychological well-being, and work stress. Data analysis using SmartPLS program. Results showed a negative and insignificant effect workload on psychological well-being with a t-value of 0.701 <1.96 and a p-value of 0.363 > 0.05. Job insecurity has a negative effect on psychological well-being with t-value of 0.483 <1.96 and p-value of 0.801 > 0.05. Workload has positive effect on work stress with t-value of 1.162 > 1.96 with p-value of 0.001 <0.05. Job insecurity has positive effect on work stress with t-value of 2.014 > 1.96 with p-value of 0.000 <0.05. Psychological well-being has negative effect on work stress with t-value of 1.050 <1.96 with p-value of 0.102 > 0.05. Results this study also concluded that positive influence workload on work stress through psychological well-being with t-value of 2,542 > 1.96 with p-value of 0.016 <0.05. Positive effect insecurity on work stress through psychological well-being with t-value of 2.038 > 1.96 with p-value of 0.042 <0.05.